Peran Sorbitol sebagai Plastisizer dalam Formulasi Masker Gel peel off Ekstrak Etanol Bunga Telang (Clitoria ternatea L.): The Function of Sorbitol as a Plasticizer on Formulation Peel-Off Gel Mask Ethanol Extract of Butterfly Flower (Clitoria ternatea L.) - Nursal, Fith Khaira; Akbar, Zahmilia; Suroso, Ratna Ayu Safitri; Aprillia Feby Farah Liza (Universitas Ngudi Waluyo, 2024)
Butterfly pea flowers (Clitoria ternatea L.) contain flavonoids that can act as antioxidants and can be used in medicine and cosmetics. One of the uses of Telang flowers in cosmetics is a peel-off gel mask. The main component of the peel-off mask formula is a plasticizer, which plays a function in determining the elasticity of the mask when it sticks to the face surface. The research objective is to formulate butterfly pea flowers in the form of extract as a peel-off gel mask with sorbitol as a plasticizer. There were four mask formulas were made using ethanol extract of butterfly pea flowers (2%) as the active ingredient, in various concentrations, namely 8% (F1), 9% (F2), 10% (F3), and 11% (F4). Mask evaluation includes organoleptic, homogeneity, pH, spreadability, viscosity, flow properties, drying time, tensile strength, and elongation. The results show that the mask meets pharmaceutical requirements with its physical gel form, average spreadability of 5 cm, and viscosity of 16244-27466 cPs. The pH value of the preparation is in the range of 5.52-5.73, by the skin's pH. The function of sorbitol as a plasticizer in peel-off masks was obtained with a drying time of ±17 minutes, as well as tensile strength values of 12.4-7.25 kg/cm2, and elongation of 350%-400%. Overall, the difference in sorbitol concentration had a significant effect on the physical evaluation of the mask (p<0.05). Differences in sorbitol concentration can increase elongation, but reduce the tensile strength of the mask. ABSTRAK Bunga telang (Clitoria ternatea L.) mengandung flavonoid yang berperan sebagai antioksidan, sehingga bisa dimanfaatkan dalam pengobatan maupun kosmetika. Pemanfaatan bunga telang dalam kosmetika salah satunya adalah masker gel peel off. Komponen utama pembentuk masker peel off adalah plastisizer, yang berperan menentukan elastisitas masker saat menempel pada permukaan wajah. Tujuan peneltiian adalah memformulasikan bunga telang dalam bentuk ekstrak sebagai masker gel peel-off dengan sorbitol sebagai plastisizer. Dibuat 4 formula masker menggunakan ekstrak etanol bunga telang (2%) sebagai bahan aktif, dalam berbagai konsentrasi yaitu; 8% (F1), 9% (F2), 10% (F3), dan 11% (F4). Evaluasi masker meliputi organoleptis, homogenitas, pH, daya sebar, viskositas, sifat alir, waktu mengering, kuat tarik dan elongasi. Hasil menunjukkan bahwa masker memenuhi persyaratan farmasetika dengan bentuk fisik gel, memiliki daya sebar rata-rata 5 cm, dan viskositas 16244-27466 cPs. Nilai pH sediaan pada rentang 5,52-5,73 yang sesuai dengan pH kulit. Peran sorbitol sebagai plastisizer pada masker peel off diperoleh waktu mengering rentang ±17 menit, serta nilai kuat tarik 12,4-7,25 kg/cm2, dan elongasi 350%-400%. Secara keseluruhan perbedaan konsentrasi sorbitol berpengaruh signifikan pada evaluasi fisik masker (p<0,05). Simpulan penelitian ini adalah perbedaan konsentrasi sorbitol dapat meningkatkan elongasi, namun menurunkan nilai kuat tarik masker.